Rancang Bangun Aplikasi Pelayanan Publik Berbasis Web Pada Kantor Kecamatan Lembak - Oriza Satifa; Iwan Setiawan; Rishi Suparianto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
Along with the development of technological advances so that the need for fast, accurate, easy and practical data processing has become a demand, so that currently the majority of institutions have utilized a computerized data management system, good service is able to provide satisfaction to the community. However, most of the service processes at the sub-district office are still carried out conventionally, namely correspondence services and data management still using a word processing program (Ms. Office), so that the process requires more time to carry out services and document documentation is not properly administered. At the Lembak District Office, one of the offices that provides administrative services is located in Lembak Village, Lembak District, Muara Enim Regency. The form of services provided relates to population administration and other services related to government at the sub-district level. The services provided are for example a cover letter for identity cards (KTP), cover letters for family cards (KK), crowd permits, incoming and outgoing letters.